EFEKTIVITAS PLATFORM DIGITAL BERBASIS GOOGLE SLIDE TERHADAP HASIL BELAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Suharto, Royyanatul Mahbubah; Hosna, Rofiatul Hosna (STAI Ma'had Aly Al-Hikam Malang, 2024)
Teachers as the frontline of the world of education must be technologically literate, keep up with the latest developments, and adjust and utilize them in learning. The world of education must adapt to this progress to improve the quality of education, especially by adjusting the use of information and communication technology in education, especially in the learning process. And educators are competing to present innovations and new colors in learning. Technology is very helpful in the learning process, the material is so easy to get, training or the learning process can be done online or anywhere, one of which is through the Google Slides platform. This study uses a quantitative approach and a type of True Experimental Design research, used to determine the scores of students from classes that are treated (experimental), and classes that are not treated (control) by improvement. Posttest Only Control Design research design. The results of the research on the Independent Sample T-Test were obtained by Sig. (2-tailed) .000 < 0.05, so there is a significant difference between the learning outcomes in class VI A as a control class that uses conventional media and class VI B as an experimental class that uses Google Slides media. And based on the results of the N-Gain score test, it shows that the average N-gain score for the experimental class (Google Slide-Based Digital Platform) is 87.11 or 87.11% included in the effective category. With an N-gain score of at least 80% and a maximum of 98%. Meanwhile, the N-gain of the control class (conventional method) has an average score of 61.68% and is included in the category of quite effective with a minimum N-gain score of 45% and a maximum score of 78%. Then H0 is rejected and HA is accepted.